Prostaglandin E2 imprints a long‐lasting effect on dendritic cell progenitors in the bone marrow. Issue 2 (27th August 2013) - Scott, Naomi M.; Ng, Royce L. X.; Gorman, Shelley; Norval, Mary; Waithman, Jason; Hart, Prue H.
Abstract : Prostaglandin E2 attenuates systemic immune responses by modulating dendritic cell progenitors in the bone marrow. Abstract : Dendritic cells (DCs) that differentiate in vitro from the bone marrow (BM) of mice with prostaglandin E2 (PGE2 )‐associated inflammation of the skin, airways, or peritoneal cavity poorly initiate immune responses. To remove in vitro differentiation and allow BM‐derived DCs to seed the periphery under steady‐state conditions, as well as study the molecule proposed responsible, chimeric mice were engrafted for >16 wk with BM cells from mice exposed to PGE2 . Serial PGE2 ‐chimeric mice were established with BM cells from the primary chimeric mice. Immune responses in the airways and skin of the PGE2 ‐chimeric mice and serial PGE2 ‐chimeric mice were significantly attenuated. After inflammatory challenges by intranasal LPS, topical fluorescein isothiocyanate, and intraperitoneal alum, DCs, macrophages, and neutrophils trafficked poorly in PGE2 ‐chimeric mice and serial PGE2 ‐chimeric mice. Injection of BM‐differentiated DCs from nonchimeric mice restored the reduced immune responses of PGE2 ‐chimeric mice. DCs from BM of 16‐wk‐engrafted PGE2 ‐chimeric and serial PGE2 ‐chimeric mice resembled cells differentiated from BM exposed to PGE2 for only 3 d, demonstrating the long‐lasting effect of PGE2 on DC progenitors. PGE2 attenuates systemic immune responses by modulating myeloid cell progenitors in the BM such that BM‐derived, terminally differentiated myeloid cells have poor trafficking ability to sites of need.